Inovasi dan Kreativitas : Pilar Utama dalam Kewirausahaan - Efiana Manilang; Ester Novita Desi; Yosia Belo (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2025)
This article discusses the importance of innovation and creativity in entrepreneurship as the main elements underlying the success of a business. Entrepreneurship is seen as a process of identifying opportunities and managing businesses aimed at creating economic and social value. Innovation, which focuses on creating new products, services or processes, and creativity, which sparks fresh ideas, are key factors in differentiating successful businesses from those that don't. These two elements support each other in creating relevant products and increasing competitiveness in the market. In facing a competitive market, entrepreneurs need to combine creativity in designing business strategies with innovation to produce solutions that can meet market needs and provide competitive advantages. This article also identifies challenges in managing innovation and creativity, such as the need for sufficient resources and time, as well as the importance of creating an environment that supports these two elements. By combining innovation and creativity, entrepreneurship can create businesses that are not only profitable, but also have a positive impact on society and the environment, and are sustainable in the future.